PENANAMAN NILAI RELEGIUS MELALUI KEGIATAN KEROHANIAN ISLAM TERHADAP SISWA MA ZAINUL HASAN 1 GENGGONG PROBOLINGGO - Herwati (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2022)
Islamic/religious spiritual activities carried out at Madrasah Aliyah Zainul Hasan Genggong Probolinggo aim to familiarize a student or group in realizing faith and piety to Allah. This study uses a descriptive qualitative method that seeks to analyze the implementation of Islamic spiritual activities so as to form the religious values ​​inherent in students. Data was collected by means of interviews, observation and documentation. The results of this study are Islamic spiritual activities become an offer and practical solution in instilling religious values ​​in students in educational institutions. In practice, it can be divided into four parts, namely daily, weekly, monthly and yearly. Through some of these activities, it has produced very significant results, namely the creation of a young generation who has a spiritual attitude and has a high awareness of religious values ​​in the surrounding environment, reduced social conflicts without blame one another. Keywords: Islamic Spiritual Activities and Religious Values